Molecular and cellular mechanisms underlying peripheral nerve injury-induced cellular ecological shifts: Implications for neuroregeneration - Limao Wu; Jinglan He; Na Shen; Song Chen (IBRO Neuroscience Reports)
The peripheral nervous system is a complex ecological network, and its injury triggers a series of fine-grained intercellular regulations that play a crucial role in the repair process. The peripheral nervous system is a sophisticated ecological network, and its injury initiates a cascade of intricate intercellular regulatory processes that are instrumental in the repair process. Despite the advent of sophisticated microsurgical techniques, the repair of peripheral nerve injuries frequently proves inadequate, resulting in adverse effects on patients' quality of life. Accordingly, the continued pursuit of more efficacious treatments is of paramount importance. In this paper, a review of the relevant literature from recent years was conducted to identify the key cell types involved after peripheral nerve injury. These included Schwann cells, macrophages, neutrophils, endothelial cells, and fibroblasts. The review was conducted in depth. This paper analyses the phenotypic changes of these cells after injury, the relevant factors affecting these changes, and how they coordinate with neurons and other cell types. In addition, it explores the potential mechanisms that mediate the behaviour of these cells. Understanding the interactions between these cells and their mutual regulation with neurons is of great significance for the discovery of new neuroregenerative treatments and the identification of potential therapeutic targets.